A Study on Matching Problems of Supersonic Two-Dimensional Air Inlets - Fakhary, I.A.; Pai, T.G. (Engineering Transactions, 1987)
In order to ensure a uniform and stable compressor face flow, maximum total pressure recovery and minimum pre-entry drag for an Air Inlet of a supersonic aircraft of flight Mach numbers above 2, over its entire flight range and variable geometry, is a necessity. The variable multi-ramp external compression two-dimensional Air Inlet is one of the most attractive solutions for this case, where variable geometry may be easier to engineer [1]. In this paper two developed computer programs (GMTRY and CRIT) are presented. OSWATITSCH [2] optimum ramp angles are used to determine the geometrical shape of the three ramp variable deflection Air Inlet, and the exact solution of the shock wave equation is utilised to determine a number of parameters relevant to the Air Inlet performance at design and critical operational conditions. Flow shape and flow pattern at critical, sub-critical and Ferri limit of the air inlet under study are presented.